Genetic diversity of hepatitis B virus and mutations associated to hepatocellular carcinoma in patients from Venezuela, with different stages of liver disease. - Puche, Mary; Kay-Valero, Sharon; Kay-Valero, Sharon; Michelli, Pedro; Michelli, Pedro; Oropeza, Maria; Oropeza, Maria; Loureiro, Carmen; Loureiro, Carmen; Devesa, Marisol; Devesa, Marisol; Dagher, Lucy; et al. (Investigación Clínica, 2016)
Abstract. Globally, about 50% of liver cancer originates as a result of long term infection with hepatitis B virus (HBV), and some genotypes and mutations have been associated with an increased severity of infection. The aim of this study was to evaluate the genetic diversity of HBV in patients from Venezuela, with chronic infection, cirrhosis and hepatocellular carcinoma (HCC) and to compare the occurrence of mutations in all patient groups. Samples from patients with different pathologies of the liver, associated with HBV infection, were collected. The HBV S region was analyzed for genotype determination and, when available, the whole genome sequence was examined for mutations analysis. Genotype F was the most common genotype (87%). While the HBV subgenotype F3 was the most frequent genotype in the whole group of samples (44%), the subgenotype F2 predominated in HCC patients (56%). Mutations were more common in HCC and cirrhosis cases (p=0.01). The A1762T mutation was significantly associated with the advanced stage of liver disease (p=0.008). Additionally, mutations were more common in early stages of liver disease in HBV subgenotype F2infected patients, and a significant association between this subgenotype and the emergence of T1753C, A1762T, A1762T/G1764A (p=0.04) and C1773T (p=0.001) mutations in chronic patients was found, when compared to the HBV subgenotype F3. By comparing F2 with all other HBV subgenotypes, a positive association for the three basal core promoter (BCP) mutants (A1762T, A1762T/G1764A p=0.01, G1764A p=0.04) was found. These results suggest that the HBV subgenotype F2 might be associated to more severe forms of liver disease in comparison with the HBV subgenotype F3.